Does the EU’s Digital Sovereignty Promote Localisation in Its Model Digital Trade Clauses? - Elaine Fahey (European Papers, 2023)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(2), 503-511 | European Forum Insight of 27 July 2023 | (Table of Contents) I. Overview. - II. On EU data localisation: On meaning, form and content. - III. The landmark transatlantic data transfer caselaw and framework - framing soft localisation? - IV. The EU’s model horizontal clauses and localisation clauses in digital trade. - V. Conclusions. | (Abstract) The EU increasingly advocates a message of tech or digital sovereignty as its future, which appears to align closely with the concept of strategic autonomy. Arguably digital sovereignty has a highly differentiated understanding in the EU as opposed to the US or China. Increasingly, many suggest EU digital sovereignty in the era of the GDPR is a high protectionist idea. Yet the EU has determined that external relations should not be at the cost of sacrificing EU data protection standards. The links of sovereignty to localisation in the context of digital trade are increasingly problematic for the EU as it seeks to reconcile high standards in the post GDPR era. The EU faced complex critique for the CJEU Schrems II ruling, for the emphasis that it places upon data localisation directly or indirectly and the manner in which it appears to awkwardly champion digital sovereignty, particularly where several EU member states practice similar levels of surveillance. The EU has developed model clauses in digital trade balancing its high GDPR standards and its external relations ambitions. The piece considers the concepts of localisation as a development of digital sovereignty in the EU’s international economic law trajectory. Arguably, the model clauses here turn out to be a template of flexibility not absolutism. Whether the EU’s model horizontal clauses reconciling the GDPR and international economic law goals cause difficult for future public policy or ultimately undermine the EU’s goals as to liberalising data flows remains to be seen.